IMPLEMENTASI REKRUTMEN DI BPS KABUPATEN LEBAK (Studi Kasus Rekrutmen Tenaga Sensus) - Yumhi Yumhi (Universitas La Tansa Mashiro, 2020)
This study aims to determine the implementation of census partner recruitment in the Central Statistics Agency of Lebak Regency in 2019 which includes the census partner recruitment process, census partner selection process, supporting factors, inhibiting factors and ways to overcome obstacles in census partner recruitment .Data collection methods in this study were by observation, interview and documentation. The data analysis technique used is descriptive analysis with a qualitative approach. The stages in the data analysis technique used are data reduction, data presentation, and drawing conclusions. The research informant chosen for the key informant is the Head of BPS of Lebak Regency who can provide complete information as well as relevant to the research objectives. While supporting informants, namely, Head of Sub-Division of Administration, Chair of Census Implementers and Employees of BPS in Lebak Regency. The data validity checking technique is done by triangulation techniques. The triangulation model used is source triangulation and method triangulation.The results showed that the implementation of census partner recruitment went through several stages, namely the acceptance of applications, administrative examinations, selection of prospective census partners, interviews, and acceptance decisions. Qualifications determined for prospective census partners are attractive appearance, maximum age of 55 years, minimum education of high school or equivalent, mastering the skills needed in the census activities offered, hard working and able to work in teams, honestly resilient and conscientious, creative and communicative. Sources of census partner recruitment come from inside and outside the Organization. Census partners who come from within the Organization through Interventions from Organic Employees. For methods from outside the applicants who submit applications to the Organization.